Clinical reasoning of the proposed method of direct prosthetic restoration in patients with generalized periodontitis - Кушлик, Андрій Петрович; Ожоган, Зиновій Романович; Палійчук, Іван Васильович (Actual Dentistry, 2019)
Aim: the objective of the research was to increase the efficiency of combination treatment of patients with partial tooth loss and generalized periodontitis using the proposed method of direct prosthetic restoration. Material and methods. All the patients were divided into 3 groups: Group I included 42 patients who immediately after tooth extraction were rehabilitated with the application of direct plastic removable laminar immediate prosthesis attached to the remaining teeth; permanent prosthetic restoration was performed 6 weeks after tooth extraction; Group II comprised 43 patients who underwent traditional prosthetic restoration using fixed dental bridges 6 weeks after mobile tooth extraction; Group III included 44 patients who immediately after mobile tooth extraction were rehabilitated with the application of direct fixed sectional dental bridge. The control group consisted of 26 people with intact dentitions.The periodontal status was studied through the determination of the periodontal index (PI), oral hygiene indices (HI-DІ-S), (HI-СІ-S), the papillary-marginal-alveolar (PMA) index, the gingival bleeding index, the degree of tooth mobility, the gingival recession index, and the combined periodontal index (CPI). The structural and functional state of bone tissue was determined by the level of bone metabolism markers; bone mineral density of the alveolar ridge in the interdental septa of the remaining teeth was determined using computer tomography. Periodontal tissues were studied before and 6 weeks after mobile tooth extraction; 6 months and 1 year after permanent prosthetic rehabilitation. Results. Oral hygiene indices, the gingival bleeding index and the PMA index were significantly better in patients treated according to the proposed method of direct prosthetic restoration in the remote period after prosthetic rehabilitation as compared to the period before treatment and group of patients who were not rehabilitated with the application of direct prosthetic restoration. Conclusion. On the basis of clinical indicators, we have proven that the use of the proposed design of direct aesthetic fixed dentures has multiple advantages over other methods of prosthetic treatment of patients with grade II generalized periodontitis. Keywords: generalized periodontitis, direct dental prosthetic restoration, bone tissue atrophy, oral hygiene indices, gingival bleeding